Age-dependent effects on radiation-induced carcinogenesis in the rat thyroid - Mutsumi Matsuu-Matsuyama (Nature Portfolio, 2021)
Abstract Childhood radiation exposure is a known thyroid cancer risk factor. This study evaluated the effects of age on radiation-induced thyroid carcinogenesis in rats irradiated with 8 Gy X-rays. We analyzed cell proliferation, cell death, DNA damage response, and autophagy-related markers in 4-week-old (4W) and 7-month-old (7M) rats and the incidence of thyroid tumors in 4W, 4-month-old (4M), and 7M rats 18 months after irradiation. Cell death and DNA damage response were increased in 4W rats compared to those in controls at 1 month post-irradiation. More Ki-67-positive cells were observed in 4W rats at 12 months post-irradiation. Thyroid tumors were confirmed in 61.9% (13/21), 63.6% (7/11), and 33.3% (2/6) of irradiated 4W, 4M, and 7M rats, respectively, compared to 0%, 14.3% (1/7), and 16.7% (1/6) in the respective nonirradiated controls. There were 29, 9, and 2 tumors in irradiated 4W, 4M, and 7M rats, respectively. The expression of several autophagy components was downregulated in the area surrounding radiation-induced thyroid carcinomas in 4W and 7M rats. LC3 and p62 expression levels decreased in radiation-induced follicular carcinoma in 4W rats. Radiosensitive cells causing thyroid tumors may be more prevalent in young rats, and abrogation of autophagy may be associated with radiation-induced thyroid carcinogenesis.